Plan de negocio ecoturístico en el municipio de Silvia Cauca (2020)
The purpose of this business plan is the evaluation of a business idea based on the provision of tourist services in the municipality of Silvia Cauca, based on ecotourism consisting of nature conservation. Using as a stage the natural and cultural resources of the Municipality. The project aims to provide new opportunities for growth to the inhabitants of Silvia and consequently to make tourists feel attracted to the place, to generate new recreation sectors for visitors. The approach of this project consists of five stages that are: the executive summary, the market study, the market plan, the technical and financial study, which will create the structure of the business idea.